Urolithin B: Two-way attack on IAPP proteotoxicity with implications for diabetes - Raimundo, Ana F.; Ferreira, Sofia; Pobre, Vânia; Lopes-da-Silva, Mafalda; Brito, José A.; dos Santos, Daniel J. V. A.; Saraiva, Nuno; dos Santos, Cláudia N.; Menezes, Regina (Frontiers in Endocrinology, 2022)
Diabetes is one of the major metabolic diseases worldwide. Despite being a complex systemic pathology, the aggregation and deposition of Islet Amyloid Polypeptide (IAPP), or amylin, is a recognized histopathological marker of the disease. Although IAPP proteotoxicity represents an important trigger of -cell dysfunction and ultimately death, its exploitation as a therapeutic tool remains underdeveloped. The bioactivity of (poly)phenols towards inhibition of pathological protein aggregation is well known, however, most of the identified molecules have limited bioavailability. Using an attractive strategy combining in silico, cell-free and cell studies, we scrutinized a unique in-house collection of (poly)phenol metabolites predicted to appear in the human circulation after (poly)phenols ingestion. With this approach, we identified urolithin B as a potent inhibitor of IAPP aggregation and a powerful modulator of cell homeostasis pathways. Urolithin B was shown to affect IAPP aggregation pattern, delaying the formation of amyloid fibrils and altering their size and morphology. The molecular mechanisms underlying urolithin B-mediated protection include protein clearance pathways, mitochondrial function, and cell cycle ultimately rescuing IAPP-mediated cell dysfunction and death. In brief, our study uncovered urolithin B as a novel small molecule targeting IAPP pathological aggregation with potential to be exploited as a therapeutic tool for mitigating cellular dysfunction in diabetes. Resulting from the colonic metabolism of dietary ellagic acid in the human body, urolithin B bioactivity has the potential to be explored in nutritional, nutraceutical, and pharmacological perspectives.